Hello from MrBillDoesMath!
Answer: f(x) = (2/3)*x -3 -- which is not a provided answer..
Discussion:
We are given that y + 7 = (2/3) * (x + 6). Multiply out the right hand side:
y + 7 = (2/3) * x + (2/3) * 6 = (2/3) *x + 12/3
= (2/3)*x + 4
Subtract 7 from both sides:
y + 7 - 7 = (2/3)*x + 4 - 7
or
y = (2/3)*x -3
Thank you,
MrB
y + 7= 2/3(x+6)
Answer:
Doodoo
Step-by-step explanation:
doodoo
Answer:
difficult but easy do it yourself you can do you can do you can do bro ...
is their a picture if not lmk
Answer:
x+2 x+2 x+2
Step-by-step explanation: